2010
DOI: 10.1063/1.3309586
|View full text |Cite
|
Sign up to set email alerts
|

A contour-mode film bulk acoustic resonator of high quality factor in a liquid environment for biosensing applications

Abstract: This letter reports an acoustic resonator of high quality factors (Qs) operating in liquid media. The film bulk acoustic resonator (FBAR) is made of a ring-shaped piezoelectric aluminum nitride thin film, and is excited in a contour mode. By having a low motional resistance upon coupling with liquids, the contour mode FBAR achieved Qs up to 189, more than 12× over the state-of-the-art FBARs in liquids. The resonator was characterized by an aptamer—thrombin binding pair for a biosensor and showed a mass resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…This increase in peak height is important because it results in a higher quality factor. Alternative modes of vibration have been used in MEMS to increase the quality factor [23-26] because a higher quality factors allows for detection of smaller shifts in resonant frequency, which will increase the sensitivity of the sensor [27]. However, there has been no report on longitudinal modes of a silicon-based microcantilever presumably due to the difficulty in exciting and detecting such a mode.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in peak height is important because it results in a higher quality factor. Alternative modes of vibration have been used in MEMS to increase the quality factor [23-26] because a higher quality factors allows for detection of smaller shifts in resonant frequency, which will increase the sensitivity of the sensor [27]. However, there has been no report on longitudinal modes of a silicon-based microcantilever presumably due to the difficulty in exciting and detecting such a mode.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 However, because of the nonuniform displacement distribution, the sensors made from the traditional FBARs with common electrode layout also present the similar problem, i.e., the drop of the quality factor caused by the generation of the compressional waves and the deviation of the frequency shifts. 21,22 Therefore, the uniform vibration displacement of FBARs eagerly needs to be achieved through the optimization of the electrode geometry and dimensions like what have been done in QCRs.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the disk-shaped resonators were most intensively investigated (Yan et al 2005;Zhang et al 2005;Xu et al 2010;Lu et al 2010Lu et al , 2011Basu and Bhattacharyya 2011;Baghelani et al 2011), because they have a high Q-factor as well as a high frequency. However, the disk-shaped resonator suffers from small amplitude and requires precise fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is believed that effective and sensitive detection of CPR levels in blood has great potential in the application of healthcare field. In Xu et al's study (Xu et al 2010), an acoustic resonator of high quality factors (Qs) was reported and a ring-shaped piezoelectric AlN thin film was made as FBAR. The resonator was characterized by an aptamer-thrombin binding pair for a biosensor and showed a mass resolution of 1.78 ng/cm 2 .…”
Section: Introductionmentioning
confidence: 99%